New Catalytic Method for the Synthesis of 2,7-Dicycloalkyl-hexaazaperhydropyrenes - Elena Rakhimova; Victor Kirsanov; Radik Zainullin; Askhat Ibragimov; Usein Dzhemilev (Journal of Chemistry)
An efficient method for the synthesis of 2,7-dicycloalkyl-2,3a,5a,7,8a,10a-hexaazaperhydropyrenes by the NiCl2·6H2O-catalyzed ring transformation reaction of 1,3,5-tricycloalkyl-1,3,5-triazines with 1,4,5,8-tetraazadecalin has been successfully developed.